Incomplete Sterility of Chromosomal Hybrids: Implications for Karyotype Evolution and Homoploid Hybrid Speciation - Lukhtanov, Vladimir A.; Dincă, Vlad; Friberg, Magne; Vila, Roger; Wiklund, Christer (Frontiers in Genetics, 2020)
Heterozygotes for major chromosomal rearrangements such as fusions and fissions are expected to display a high level of sterility due to problems during meiosis. However, some species, especially plants and animals with holocentric chromosomes, are known to tolerate chromosomal heterozygosity even for multiple rearrangements. Here, we studied male meiotic chromosome behaviour in four hybrid generations (F1 to F4) between two chromosomal races of the Wood White butterfly Leptidea sinapis differentiated by at least 24 chromosomal fusions/fissions. Previous work showed that these hybrids were fertile, although their fertility was reduced as compared to crosses within chromosomal races. We demonstrate that (i) F1 hybrids are highly heterozygous with nearly all chromosomes participating in the formation of trivalents at the first meiotic division, and (ii) that from F1 to F4 the number of trivalents decreases and the number of bivalents increases. We argue that the observed process of chromosome sorting would, if continued, result in a new homozygous chromosomal race, i.e. in a new karyotype with intermediate chromosome number and, possibly, in a new incipient homoploid hybrid species.